2008
DOI: 10.1016/j.str.2007.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Fibrin Clot Elasticity

Abstract: Blood clots must be stiff to stop hemorrhage yet elastic to buffer blood's shear forces. Upsetting this balance results in clot rupture and life-threatening thromboembolism. Fibrin, the main component of a blood clot, is formed from molecules of fibrinogen activated by thrombin. Although it is well known that fibrin possesses considerable elasticity, the molecular basis of this elasticity is unknown. Here, we use atomic force microscopy (AFM) and steered molecular dynamics (SMD) to probe the mechanical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
121
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(134 citation statements)
references
References 65 publications
9
121
0
4
Order By: Relevance
“…Brown and coworkers used atomic force microscopy to study the forced unfolding of engineered linear oligomers of fibrinogen to elucidate the elastic properties of blood clots 141 . More recently, Lim and coworkers showed that the elastic properties of blood clots are mainly determined by the coiled-coil helices of fibrinogen 142 . In another example, Kellermayer and coworkers described the structure and self assembly mechanism of amyloid β-fibrils 143 and myosin thick filaments 144 .…”
Section: Applications Of Afmmentioning
confidence: 99%
“…Brown and coworkers used atomic force microscopy to study the forced unfolding of engineered linear oligomers of fibrinogen to elucidate the elastic properties of blood clots 141 . More recently, Lim and coworkers showed that the elastic properties of blood clots are mainly determined by the coiled-coil helices of fibrinogen 142 . In another example, Kellermayer and coworkers described the structure and self assembly mechanism of amyloid β-fibrils 143 and myosin thick filaments 144 .…”
Section: Applications Of Afmmentioning
confidence: 99%
“…However, we have known little about the details of folding and unfolding process for CLN025 yet. In this paper, we study the unfolding of CLN025 by mechanical stretching using steered molecular dynamics (SMD) simulation, which mimics AFM experiment and reveals the molecular mechanisms underlying mechanical function (Guzmán et al 2008(Guzmán et al , 2009Lu and Schulten 1999;Hamdi et al 2008;Rief et al 1997;Lim et al 2008;Zeng et al 2010). Because of computational limits, the pulling velocities used in SMD are orders of magnitude higher than those in an AFM experiment, leading to drastic overestimation of the unfolding forces.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 The overall mechanical properties of fibrin are determined by structural features at the level of the molecule, individual fibers, and the branched fiber network. [11][12][13] Fibrin cross-linking by activated factor (F)XIII improves the elastic properties and resistance to fibrinolysis. 14 -17 ␥-Chain cross-links occur between lysine 406 on one chain and either glutamine 398 or 399 on another.…”
mentioning
confidence: 99%